The lactylation-immunosuppression network in cancer: driving a metabolic-epigenetic axis - Ye, Jinfeng; Lu, Yunliang; Huang, Wansu; Huang, Shan; Zhang, Zhe; Zhou, Xiaoying; Xiao, Xue; Huang, Tingting (Frontiers in Immunology, 2026)
The accumulation of lactate in the tumor microenvironment (TME), driven by the Warburg effect, is closely associated with immunosuppression. Lactate can contribute to this process through lysine lactylation, a novel post-translational modification. We propose a conceptual framework, the “Lactylation-immunosuppression network,” that links tumor metabolic reprogramming to immune cell signaling and gene expression. This network highlights a metabolic-epigenetic axis linking lactylation to immunosuppression via a synergistic dual mechanism: long-term epigenetic programming via histone lactylation establishes a stable immunosuppressive transcriptome, while rapid, dynamic non-histone lactylation directly modulates protein activity and stability, thereby potentiating function. This review summarizes how lactylation may undermine anti-tumor immunity by remodeling myeloid and T cell compartments, fortifying immune checkpoint barriers, and creating self-reinforcing metabolic feedback loops. By elucidating this mechanism, we highlight novel therapeutic targets, propose a “kinetic threshold” model to resolve the paradoxical role of lactate, and provide a unified conceptual framework for developing next-generation immunotherapies and guiding future mechanistic studies.